Contaminantes emergentes em estações de tratamento de esgoto aeróbia e anaeróbia - Grosseli, Guilherme Martins (2016)
The wastewater treatment plant (WWTPs) play an important role to ensuring the health and preservation of aquatic ecosystems through biological removal (mainly) of pollutants and microorganisms in the sanitary and industrial sewage, avoiding the disposal "in natura" of sewage on water and soil. Among these organic contaminants stand out Emerging Contaminants (EC), like pharmaceuticals, personal care products and endocrine disruptors, drug abuse, etc.In this study, it was investigated the occurrence and evaluated the removal of 12 EC: naproxen (NPX), diclofenac (DCF), ibuprofen (IBU), caffeine (CAF), carbamazepine (CBZ), propranolol (PRP), atenolol (ATL ), 1-hydroxyibuprofen (IBU-1OH), 2-hydroxy-ibuprofen (IBU-2OH), 10,11-dihydro-10,11-dihydroxy-carbamazepine (CBZ-DIOH), 2-hydroxy-carbamazepine (CBZ-2OH) at two wastewater treatment plants operating with biologic system, one aerobic and another one anaerobic. The first one is located in Jundiaí / SP city and the second one in São Carlos / SP. The target compounds were extracted from the aqueous phase by solid phase extraction (SPE). The analytical determinations were done through liquid chromatography coupled to mass spectrometry with triple quadrupole analyzer (UPLC-MS / MS).Pharmaceuticals, metabolites and personal care product triclosan were detected in all samples. The WWTP CSJJundiaí, which operates in aerobic system showed high removal values (R>70%), in all samples, for the CAF, NPX, ATL, IBU-1OH and TCS, moderate removal (70%>R> 20%) for the IBU and IBU-2 OH, low removal (R <20%) and production (R <0%) for CBZ and PRP.On the other hand ETE-Monjolinho, which operates in an anaerobic system presented a less removal of contaminants, where only caffeine had R> 70%.Thecompounds TCS IBU-2OH, IBU-1OH and ATL was moderate removal, CBZ-DIOH, CBZ and IBU was poorly removal, while it was observed production of DCF, PRP and CBZ-2OH (R < 0%). The metabolite CBZ-DIOH was recalcitrant to degradation in both WWTP. Moreover, it was noticed that WWTP can not only promote the degradation of some contaminants but also the production of the same, as is the case of DCF, CBZ, CBZ-2OH, CBZ-DIOH and PRP in both WWTP, and Moreover, it is possible to observe that STPs can promote not only the degradation of some contaminants but also the production of the same, as is the case of DCF, CBZ, CBZ-2 OH, CBZ-DIOH and PRP in both STPs, and ATL, IBU, and IBU-1OH only in ETE-Monjolinho. Despite both WWTP not completely remove the organic contaminants, it was found that WWTP with aerobic biodegradation has proved more effective in removing the EC than anaerobic biodegradation.The currently WWTP technologies are not able to eliminated most of EC, providing this contaminants into water bodies. This work aim to contributes to the understanding the EC in WWTP, in order to support better operating parameters of WWTP or the requirement of new technologies which allowed the removal of these contaminants providing treated wastewater that could helping for the global water scarcity problem.